Evaluation Of Total Quality Management (TQM) In Improving The Quality Of Graduates: Case Study On Motorcycle Engineering And Business Study Program At Vocational High School In Bandung - Yusi Roslina Suciati; Arlette Suzy Puspa Pertiwi; Mira Veranita (Majalah Bisnis & IPTEK, 2025)
Graduates of Vocational High Schools (SMK) play a crucial role in fulfilling the workforce requirements of the industrial sector. This condition represents a strategic opportunity for SMK to provide students with technical skills and moral fortitude, preparing them to become competent employees. This study seeks to assess the application of Total Quality Management (TQM) in enhancing the quality of graduates, particularly within the Motorcycle Engineering and Business Study Programme at a vocational school in Bandung. The study concentrates on the strategy for implementing Total Quality Management (TQM), the evaluation procedures for TQM, the factors that facilitate or impede TQM implementation, and the ways to address these challenges. This study employs a qualitative methodology utilizing a case study approach, with data gathering conducted via in-depth interviews, direct observation, and pertinent document analysis. The study's findings suggest that the Total Quality Management implementation strategy commences with a comprehensive understanding of the organization's vision and mission, which guide its objectives. This is reinforced by human resource development, the provision of sufficient facilities and infrastructure, the enhancement of a curriculum aligned with industry requirements, the cultivation of positive attitudes, and the establishment of a supportive learning environment. The processes for evaluating TQM involve establishing a collective commitment to enforce discipline, cultivating accountability, and sustaining concentration on attaining primary objectives. Factors that facilitate TQM implementation include skilled human resources, comprehensive facilities, a flexible curriculum, and a conducive learning environment. Concurrently, impediments consist of restricted human resources, inadequate facilities, and a deficiency in comprehensive comprehension of the TQM concept among all stakeholders within the school. The adopted method to address these challenges is to align all organizational components, including leaders, educators, and students, with the school's vision and goal, fostering a robust quality culture within the educational environment. This study concludes that a robust integration of human resources, facilities, curriculum, and an effective learning environment can attain the caliber of vocational high school graduates. Consequently, vocational high school graduates possess standardized abilities that align with the requirements and expectations of the business and industrial sectors (DUDI), rendering them a workforce prepared to participate effectively.